Effect of position on transdiaphragmatic pressure and hemodynamic variables in anesthetized horses - Youngblood, Cori (Kansas State University, 2019)
Recumbency affects respiratory mechanics and oxygenation in anesthetized horses. Changes in pleural and abdominal pressures that can impair ventilation have not been described in all recumbencies. The objective of this study was to determine the effects of patient positioning on transdiaphragmatic pressures and selected hemodynamic variables. Horses were maintained under total intravenous general anesthesia with nasal oxygen supplementation. Trans-nasal balloon catheters connected to pressure transducers placed within the stomach and thoracic esophagus were used to measure intrathoracic and gastric pressure in standing and anesthetized horses positioned in: right and left lateral recumbency, dorsal recumbency, reverse Trendelenburg position, and Trendelenburg position. Transdiaphragmatic pressures were calculated as the difference between gastric and intrathoracic pressure. Measurements of SpO₂, heart rate, systolic, diastolic and mean arterial pressure, and respiratory rate were obtained every 5 minutes. When compared to dorsal recumbency, gastric expiratory pressure is decreased in the standing position. Thoracic expiratory pressure is decreased in standing and reverse Trendelenburg. Transdiaphragmatic expiratory pressure and SpO₂ are decreased in Trendelenburg. Heart rate is increased in reverse Trendelenburg. Systolic, diastolic, and mean arterial pressures are decreased in reverse Trendelenburg and increased in left lateral and right lateral. We found there is wide variation in respiratory pressures between horses and positions and they are not predictive of associated changes in hemodynamic variables.
Keywords: Horse; Pressure; Diaphragm; Trendelenburg; Hemodynamic